2008
DOI: 10.1055/s-2008-1066570
|View full text |Cite
|
Sign up to set email alerts
|

Nebenwirkungen der antithyreoidalen Therapie der Hyperthyreose: Eine Untersuchung an 1256 fortlaufend betreuten Patienten

Abstract: Side effects of antithyroid treatment were retrospectively analysed in 1256 patients with hyperthyroidism. Overall rate of side effects was 14.3%. Skin reactions were the most frequent ones (5.6%), followed by arthropathies (1.6%). The incidence of agranulocytosis was 0.14%. Median duration of all side effects was 1.5 months. In half the cases the side effects were controllable so that treatment was continued, although at a changed dosage. The rate of cross-reaction between carbimazole and thiamazole, on the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The 2 groups of patients were observed in both high and low doses regimen. Recently, Meyer-Gebner et al (1989) found high toxicity rate in patients taking over 20 mg of thiamazol or over 30 mg daily of carbimazole. It is very difficult to find a satisfactory explanation for the discrepancy between our findings and the data of Meyer-Gebner et al (1989).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 groups of patients were observed in both high and low doses regimen. Recently, Meyer-Gebner et al (1989) found high toxicity rate in patients taking over 20 mg of thiamazol or over 30 mg daily of carbimazole. It is very difficult to find a satisfactory explanation for the discrepancy between our findings and the data of Meyer-Gebner et al (1989).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Meyer-Gebner et al (1989) found high toxicity rate in patients taking over 20 mg of thiamazol or over 30 mg daily of carbimazole. It is very difficult to find a satisfactory explanation for the discrepancy between our findings and the data of Meyer-Gebner et al (1989). They studied a population of hyperthyroid patients that included toxic multinodular goiter that are often older than Basedow's disease patients.…”
Section: Methodsmentioning
confidence: 99%
“…Other major adverse effects include acute liver failure (for which PTU has a black box warning), hypothyroidism, ANCA associated vasculitis, hypersensitivity reaction (Steven Johnson syndrome, toxic epidermal necrolysis, and urticaria). 4 , 5 Mild and more prevalent side effects are fever, arthralgias, and lymphadenopathy. Cholestatic jaundice, lupus-like syndrome, hypergammaglobulinemia, taste and smell abnormalities, sialadenitis, myopathy, and hair loss are less frequent side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Antithyroid drugs are associated with side effects in both cats and humans. 28 Furthermore, antithyroid medication could be potentially teratogenic and, although owners should handle antithyroid medication with care, this recommendation does not always seem to be followed. 811 Currently, no studies have qualified and quantified the urinary excretion of thiamazole in cats in combination with a risk assessment of direct or indirect exposure for the owners.…”
Section: Introductionmentioning
confidence: 99%